Uptake and availability of new outpatient cancer medicines in 2010-2021 in Nordic countries - survey of competent authorities - Kati Sarnola; Hanna Koskinen; Katariina Klintrup; Cecilie Astrup; Terhi Kurko (BMC, 2023)
Abstract Background Nordic countries excel in cancer care, but studies on uptake, costs, or managed entry agreements of cancer medicines have not been conducted recently. The aim of this study was to examine the uptake and availability of orally administered new cancer medicines in Nordic countries. Orally administered cancer medicines enable and are used in the community as part of outpatient care. Firstly, we studied the distribution, costs and adoption of managed entry agreements of these medicines, and secondly, uptake of and managed entry agreements for cancer medicines used in outpatient care that were granted marketing authorization in Europe in 2010-2021. Methods An E-mail survey of competent authorities, meaning pharmaceutical service organizers, payers or other government or non-government actors developing pharmaceutical service operations, in Denmark, Finland, Iceland, Norway, and Sweden in April-June 2022. The data were analysed using frequencies and percentages for descriptive analysis. Results The distribution of cancer medicines has similarities in Finland, Iceland, Norway, and Sweden, where cancer medicines can be distributed both via hospitals or hospital pharmacies for inpatient use, and via community pharmacies for outpatient use. In Denmark, cancer medicines are predominantly distributed via publicly funded hospitals. In all countries that provided data on the costs, the costs of cancer medicines had notably gone up from 2010 to 2021. The number of reimbursable medicines out of new cancer medicines varied from 36 products in Denmark and Iceland to 51 products in Sweden, out of 67 studied products. Managed entry agreements, often with confidential discounts, were in use in all Nordic countries. The number of agreements and the cancer types for which agreements were most often made varied from three agreements made in Iceland to 35 agreements made in Finland, out of 67 studied products. Average days from authorization to reimbursement of new cancer medicines varied from an average of 416 to 895 days. Conclusions Nordic countries share similar characteristics but also differ in terms of the details in distribution, adopted managed entry agreements, market entry, and availability of new orally administered cancer medicines used in the outpatient care. The costs of cancer medicines have increased in all Nordic countries during the last decade. Due to differences in health care and because orally administered cancer medicines can be dispensed at community and hospital pharmacies in all studied countries other than Denmark, the number of reimbursable medicines and managed entry agreements vary between countries. However, Nordic countries show good agreement for 2010 to 2021 in entry and reimbursement decisions of novel cancer medicines.